Hubungan Abnormalitas Persalinan Dengan Faktor Risiko Autistik - Bani Zakiyah; Aris Sudiyanto; Adji Suwandono (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2014)
Background: Autism is a disorder affects communication, social, language, and behaviour impairments of children. The prevalence of autism tend to increase, but its etiology still unclear and multifactoral suspected. Based on some studies, the incidence of autism were increase if there are some problems in prenatal, natal, or postnatal. Abnormality labor is one of the problem in natal that suspected has a correlation with autism. This study aims to determine the correlation between abnormal labor and risk factors of autism. Methods: This study was an analytic observational study with case control design. The subject were taken by porposive random sampling in case group and control group. The interview done in 66 mothers of children. 33 children taken from SLB Autis Harmony, SLB Autis Agca Center, SLB Autis Alamanda, and SLB-B C dan Autis YBA Surakarta as case group and 33 children taken from SDN Ngoresan Surakarta as control group. Then the results were tested with Chi Square through SPSS 17.0 for Windows. Results: From the case group, 90.9% were born with abnormal labor and from the control group, 48.5% were born with abnormal labor. The result of Chi Square analysis, the value p < 0.01, it means the probability value is lower than 0.05. So, there is significal correlation between abnormal labor and risk factors of autism. Conclusions: The conclusion of this research is there is correlation between abnormal labor and risk factor of autism. Keywords: abnormal labor, risk factors, autism